2023
DOI: 10.1002/aenm.202203154
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Charging Mechanisms and the Coupled Structural–Mechanical Behavior of Ti3C2Tx (MXenes) Electrodes by In Situ Techniques

Abstract: The discovery of the Ti3C2Tx compounds (MXenes) a decade ago opened new research directions and valuable opportunities for high‐rate energy storage applications. The unique ability of the MXenes to host various mono‐ and multivalent cations and their high stability in different electrolyte environments including aqueous, organic, and ionic liquid solutions, promoted the rapid development of advanced MXene‐based electrodes for a large variety of applications. Unlike the vast majority of typical intercalation co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…[65] Upon cation insertion either by potential application or by spontaneous ions exchange, the interlayer distance between the adjacent layers varies depending on the size and the valence of the intercalated ions. [57] It is reported that among twelve of the metal ion intercalants, the nanopillar effect of Be 2 + greatly enhanced the charge-transfer process of the obtained Be 2 + -MXene electrode with minimal decrease in the electrolyte diffusion rates. [66] More recently, Water-in-salt (WIS) electrolytes have been explored to increase the operating potential windows of MXene electrodes.…”
Section: Neutral and Alkaline Electrolytementioning
confidence: 95%
See 3 more Smart Citations
“…[65] Upon cation insertion either by potential application or by spontaneous ions exchange, the interlayer distance between the adjacent layers varies depending on the size and the valence of the intercalated ions. [57] It is reported that among twelve of the metal ion intercalants, the nanopillar effect of Be 2 + greatly enhanced the charge-transfer process of the obtained Be 2 + -MXene electrode with minimal decrease in the electrolyte diffusion rates. [66] More recently, Water-in-salt (WIS) electrolytes have been explored to increase the operating potential windows of MXene electrodes.…”
Section: Neutral and Alkaline Electrolytementioning
confidence: 95%
“…Additionally, Ti 3 C 2 T x films in acidic environments (1 M H 2 SO 4 ) reveal a potentially dependent gravimetric response, attributed to the varied hydration state of the inserted protons [64] . Based on DFT calculations it was found that the presence of water between the MXene layers facilitates its charging kinetics by providing a hydrogen‐bonded water network for fast proton diffusion [57] …”
Section: Electrochemical Reaction Mechanism Of Mxenementioning
confidence: 99%
See 2 more Smart Citations
“…However, the widespread implementation of in situ techniques in MXenes research is still underway, and techniques such as in situ SEM and in situ TEM remain underutilized for studying MXenes. [ 163 ] Furthermore, certain novel MXenes (e.g., V‐based, Nb‐based, and Mo‐based MXenes) have received limited attention in terms of their applications and underlying mechanisms, with insufficient documentation. Therefore, it is crucial for future scientific research to integrate in situ techniques more extensively and accurately with traditional ex situ techniques.…”
Section: Structure‐property Relations In Mxenesmentioning
confidence: 99%